MODEL PENGELOLAAN SAMPAH BERBASIS MASYARAKAT DI KOTA DENPASAR - Made Armadi; Wayan Suarna; Made Sudarma; Made Sudiana Mahendra; Nyoman Sudipa (Master Program of Environmental Science, Postgraduate Program of Udayana University, 2020)
Garbage is a problem that must be faced by the community, because garbage is a form of environmental pollution, where garbage can have an impact on public health, such as; odors, floods, destroy aesthetics, fire, greenhouse effect and so on. Household waste management requires active community participation so that the role of the government does not get heavier. Increase community participation in waste management in Denpasar City. In an effort to build the effectiveness of waste management in Denpasar City, it is necessary to develop a community-based waste management model in Denpasar City. The purpose of developing a waste management model is to actively involve the community in managing waste in Denpasar City. This study uses the Interpretative Structural Modeling (ISM) method approach by using elements of the affected community, elements of program objectives, elements of indicators to achieve goals, elements of the main constraints and elements of the institutions involved. In compiling the sub-elements from each element, it involves figures, experts, actors and activists in Denpasar City on community-based waste management. The results of the modeling show that the participatory role of the community is very important in reducing waste through reuse, increasing community involvement and implementing 3R activities. The main obstacle in waste management is the limited facilities and infrastructure for waste management and the unclear waste management organization. Possible changes are that law enforcement and waste regulations must be clear and the involvement of all stakeholders in community-based waste management in Denpasar City. Keywords: model; management; waste; society.